End-of-life decisions: A focus group study with German health professionals from human and veterinary medicine - Selter, Felicitas; Persson, Kirsten; Kunzmann, Peter; Neitzke, Gerald (Frontiers in Veterinary Science, 2023)
At first glance, human and (companion animal) veterinary medicine share challenging processes in end-of-life (EOL) decision-making. At the same time, treatment options in both professions are substantially different. The potential of an interdisciplinary exchange between both fields has been neglected by empirical research so far. In this qualitative study, professionals from both fields were brought together in interdisciplinary focus groups to investigate the ethical aspects of convergences and divergences in EOL situations in human and veterinary medicine. The authors present and discuss an innovative mix of materials and methods as stimuli for discussion and for generating hypotheses. The results point towards a general convergence of issues, challenges, and judgements in EOL situations in both fields, such as professional ethos, communication with the family and the role thereof as well as the ideals of death, clearly exceeding the expectations of study participants. At the same time, the study highlights a few prominent differences such as the access to patients’ preferences or legal and practical constraints. The findings suggest that using social science methods in empirical interdisciplinary biomedical-veterinary ethics could help to shed more light on this new area. Animal as well as human patients can potentially benefit from this mutual, scientifically accompanied exchange and the resulting corrections or completions of misconceptions.